Immunohistochemical and clinicopathologic features of estrogen receptor-negative, progesterone receptor-positive, HER-2 negative breast carcinomas - Nardi,Rosana Pellin De (2021)
SUMMARY OBJECTIVE: Currently, there is an ongoing debate whether progesterone receptor positive and estrogen receptor negative breast carcinomas represent a true distinct subtype of tumor or a mere immunohistochemical artifact. In this study, we conducted an immunohistochemistry panel with the antibodies TFF1, EGFR, and CK5 to reclassify this phenotype in a luminal or basal-like subtype. METHODS: Tumors estrogen receptor -/progesterone receptor +, Her-2 – from a large population of breast cancer patients were selected to be studied. Immunohistochemistry with the antibodies TFF1, EGFR, and CK5 was performed. Tumors showing positivity for TFF1, regardless of EGFR and CK5 results, were classified as luminal-like carcinomas. Those lesions that were negative for TFF1, but were positive for EGFR and/or CK5, were classified as basal-like triple-negative carcinomas. When the three markers were negative, tumors were classified as undetermined. Clinical pathologic characteristics of patients and tumor recurrence were evaluated. RESULTS: Out of 1188 breast carcinomas investigated, 30 cases (2.5%) presented the estrogen receptor -/progesterone receptor +/HER2- phenotype. Of them, 27 tumors (90%) were classified as basal-like triple-negative carcinomas, one as luminal-like (3.3%), and two as undetermined tumors (6.7%). The mean follow-up for the study group was 27.7 (2.7 to 50) months. Out of the 26 patients, 6 had cancer recurrence: 2 local and 4 systemic recurrences. The average time for recurrence was 17 (8 to 38) months. CONCLUSION: Estrogen receptor -/progesterone receptor +/tumors exhibit aggressive behavior, similar to triple-negative tumors. An appropriate categorization of these tumors should be made to improve their therapeutic management.